Handbook on the science of early literacy - Cabell, Sonia Q.; Dickinson, David K.; Neuman, Susan B.; Terry, Nicole Patton (New York The Guilford Press, 2023)
"Synthesizing the best current knowledge about early literacy, this comprehensive handbook brings together leading researchers from multiple disciplines. The volume identifies the instructional methods and areas of focus shown to be most effective for promoting young children's growth in reading, writing, oral language, and the connections among them. In 33 chapters, the Handbook covers conceptual foundations; development and instruction of both code- and meaning-related literacy skills; professional development and family engagement; supporting equity across populations; and learning beyond traditional boundaries, including digital and out-of-school contexts"--
Simplicity meets complexity : expanding the simple view of reading with the direct and indirect effects model of reading / Young-Suk Grace Kim -- Early environmental influences on language / Meredith L. Rowe, Rachel R. Romeo, and Kathryn A. Leech -- Prioritizing dual language learners' language comprehension development to support later reading achievement / Jeannette Mancilla-Martinez -- Early literacy, response to intervention, and multi-tiered systems of support / Dayna Russell Freudenthal, Mai W. Zaru, and Stephanie Al Otaiba -- The neuroscience of early literacy development / Rachel R. Romeo -- Learning the code / Barbara R. Foorman -- The science of early alphabet instruction : what we do and do not know / Shayne B. Piasta -- Invented spelling : an integrative review of descriptive, correlational, and causal evidence / Monique Sénéchal, Gene Ouellette, and H.N. Lam Nguyen -- Early spelling development : influences, theory, and educational implications / Nenagh Kemp and Rebecca Treiman -- Supporting students' early writing development through data-based instruction / Kristen L. McMaster, Seyma Birinci, Emma Shanahan, and Erica Lembke -- Language is the basis of skilled reading comprehension / Laura M. Justice and Hui Jiang -- Language interventions in early childhood : summary and implications from a multistudy program of research / Beth M. Phillips -- Content literacy : integrating social studies and language / Sharolyn D. Pollard-Durodola and Jorge E. Gonzalez -- Supporting integrated instruction in science and literacy in K-2 classrooms / Tanya S. Wright and Amelia Wenk Gotwals -- Leveraging content-rich English language arts instruction in the early grades to improve children's language comprehension / Sonia Q. Cabell and HyeJin Hwang -- Feeding two birds with one hand : instructional simultaneity in early literacy education / Nell K. Duke, Julia B. Lindsey, and Crystal N. Wise -- Comprehension : from language to reading / Ellen Orcutt, Victoria Johnson, and Panayiota Kendeou -- Measuring and improving teachers' knowledge in early literacy / Anne E. Cunningham, Allison R. Firestone, and Mónica Zegers -- Professional development in early language and literacy : using data to balance effectiveness and efficiency / Annemarie H. Hindman and Barbara A. Wasik -- Using the science of early literacy to design professional development for writing / Hope K. Gerde and Gary E. Bingham -- Structuring adaptations for scaling up evidence-based literacy interventions / James S. Kim and Douglas M. Mosher -- Together we can do so much : aligned school and home efforts using a multi-tiered system of support framework / Tricia A. Zucker, Gloria Yeomans-Maldonado, Sarah Surrain, and Susan H. Landry -- Family engagement for early literacy : interventions that promote family-school partnerships / Karalynn E. Brown and Susan M. Sheridan -- Literacy architectures : making the case for systems of learning and teaching to cultivate readers and writers in linguistically diverse schools / Emily Phillips Galloway and Nonie K. Lesaux -- The development of early orthographic representations in children : the lexical asymmetry hypothesis and its implications for children with dyslexia / Donald L. Compton, Laura M. Steacy, Nuria Gutiérrez, Valeria M. Rigobon, Ashley A. Edwards, and Nancy C. Marencin -- Developmental language disorder : what it is and why it matters / Maura Curran and Tiffany Hogan -- Autism and early literacy : the state of the science / Kelly Whalon and Veronica P. Fleury -- Multi-tiered systems of support : an approach for reducing disparities in school readiness and increasing equity in early literacy and learning opportunities for young children / Judith J. Carta and Charles R. Greenwood -- Factors associated with Black children's early development and learning / Iheoma U. Iruka, Amber B. Sansbury, Nicole A. Telfer, Nneka Ibekwe-Okafor, Nicole Gardner Neblett, and Tonia R. Durden -- Early literacy in everyday spaces : creating opportunities for learning / Susan B. Neuman -- Digital picture books : opportunities and utilities / Adriana G. Bus and Trude Hoel -- E-books with a digital dictionary as a support for word learning / Ofra Korat and Ora Segal-Drori -- Leveraging research-practice partnerships to support evidence use in early childhood : lessons learned from Atlanta 323 / Nicole Patton Terry, Gary E. Bingham, Anita Faust Berryman, Janelle Clay, and Kate Caton.
Includes bibliographical references and index.
Keywords: Language arts (Early childhood); Early childhood education -- Research